2017
DOI: 10.1371/journal.pone.0169516
|View full text |Cite
|
Sign up to set email alerts
|

Association between NF-κB Pathway Gene Variants and sICAM1 Levels in Taiwanese

Abstract: Intercellular adhesion molecule–1 (ICAM1) is crucial to the development and progression of atherosclerosis. Recent genome-wide association studies (GWAS) have revealed that single nucleotide polymorphisms (SNPs) in two of the nuclear factor-κB (NF-κB) pathway genes, NFKBIK and RELA, are associated with soluble ICAM1 (sICAM1) levels. However, neither of these two gene variants is found in the Asian populations. This study aimed to elucidate whether other candidate gene variants involved in the NF-κB pathway may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…2015), and performs other functions that can alter the neurological processes in the brain. This scenario is in line with the results obtained by Wu et al. (2017), who suggested that NKAPL rs1635 (T152N mutation) may be related to central nervous system development and significantly associated with the plasma levels of Intercellular adhesion molecule–1 (sICAM1), an important cell adhesion molecule with essential roles in inflammatory processes.…”
Section: Discussionsupporting
confidence: 91%
“…2015), and performs other functions that can alter the neurological processes in the brain. This scenario is in line with the results obtained by Wu et al. (2017), who suggested that NKAPL rs1635 (T152N mutation) may be related to central nervous system development and significantly associated with the plasma levels of Intercellular adhesion molecule–1 (sICAM1), an important cell adhesion molecule with essential roles in inflammatory processes.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we found that silencing pulmonary HMVEC‐CDH13 significantly decreased whole cell ICAM‐1 and demonstrated a decreased ICAM‐1 surface expression in the PBS‐treated group and a decreased trend in the LPS‐treated group. A Genome‐Wide Association Study in the Taiwanese population showed an association between CDH13 risk alleles and increased soluble ICAM‐1 (Wu et al, 2017 ), supporting a mechanistic interaction between CDH13 and ICAM‐1 expression. CDH13 has also been shown to be elevated in early atherosclerosis (Philippova et al, 2011 ), and ICAM‐1 has been found to be crucial for the development of atherosclerosis (Lawson & Wolf, 2009 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…While most studies including the present one examine the acute effects of BYHW on stroke, the effects of chronic treatment of BYHW are yet to be fully elucidated. Long-term effects of BYHW on suspected genes or target proteins related to inflammation and mitochondria homeostasis in ischemic stroke and peripheral artery diseases also warrant further research [9,26,27,28].…”
Section: Discussionmentioning
confidence: 99%